Impact of Photovoltaic Panel Orientation and Elevation Operating Temperature on Solar Photovoltaic System Performance - Ebhota, Williams S.; Tabakov, Pavel Y (International Journal of Renewable Energy Development, 2022)
This study conducts optimum tilt angle and orientation of a standalone c-Si monocrystalline solar photovoltaic (PV) system deploying PVsyst software. The site of the hypothesized solar PV system is at 9, Mountain Rise, Berea, Durban, South Africa. This work presents values of tilt and azimuth angles and battery operating temperature that support optimal solar PV system performance. The range of angles considered for tilt and azimuth for a fixed PV panel mounting is 0° to 90° and -100° to 100°, respectively. Based on the report obtained from PVsyst design and simulation software, this study finds that: the highest available energy, specific energy, used energy, solar fraction, and lowest loss were recorded at tilt 40° and Azimuth 0°. Further, the longest battery service life was attained at an operating temperature between -2 °C to 20 °C. Hence, 40° and 0° are the optimum tilt and Azimuth angles, respectively while running the storage system at a temperature, not more than 20 °C.